We're Not There Yet. (May 2014) - Eibling, David
Patient injury due to medical error continues to plague health care delivery. Efforts to eliminate errors or mitigate their effects have largely been thwarted, despite enormous investments of human and financial resources. A survey published in this issue of Otolaryngology–Head and Neck Surgery on the status of medical error in otolaryngology finds that the specialty is not exempt. The authors report that relatively little has changed since the original report by the senior authors published a decade ago. Despite this lack of apparent progress, there is growing awareness that improvements in patient safety will be incremental rather than transformational. The author of this commentary identifies a number of fundamental cultural changes that will be required to achieve transformational change.